Pengaruh Kedisiplinan Dan Kerjasama Terhadap Produktivitas Kerja Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Wilmar Nabati Padang - Hayuda Akbari; Ramdani Bayu Putra; Nia Nadilla (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine and try to analyze the influence of discipline and cooperation on work productivity with job satisfaction as an intervening variable at PT. Wilmar Nabati Padang. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are employees of PT. Wilmar Nabati Padang. The research results found that there is an influence between discipline and job satisfaction. There is an influence between Collaboration on Job Satisfaction. There is an influence between discipline and work productivity. There is no influence between Collaboration on Work Productivity. There is an influence between Job Satisfaction and Work Productivity. Job Satisfaction mediates Discipline on Work Productivity. Job Satisfaction mediates Collaboration on Work Productivity.